Non-invasive assessment of extracranial–intracranial bypass grafts using advanced ultrasound technology. Issue 5 (1st November 2002) - Birchall, D; English, P; Tacconi, L
Abstract : There have been significant developments in ultrasound technology in the last few years which have resulted in an increase in the clinical value of this technique. An illustrative case is presented of how ultrasound technology has been used in the intraoperative and postoperative period to evaluate graft patency and function in patients undergoing extracranial–intracranial bypass graft surgery.